Primary hypertriglyceridemia in children with familial chylomicronemia syndrome - Jumantan, Dewi; Widowati, Titis; Hidayati, Irma Sri; Prawirohartono, Endy P. (Paediatrica Indonesiana, 2024)
Hypertriglyceridemia can be caused by primary (genetic) or secondary etiology. One of the primary causes is hyperlipoproteinemia type I or known as familial chylomicronemia syndrome. Familial chylomicronemia syndrome is a rare autosomal recessive disease that occurs in 1-2 per 1,000,000 people, with specific characteristic signs, namely severe increment of fasting plasma triglyceride up to 100 times the normal value (about 1500-15,000 mg/dl) caused by lipoprotein lipase (LPL) mutation.